Do thank-you calls increase charitable giving? Expert forecasts and field experimental evidence - Samek, Anya and Longfield, Chuck (American Economic Journal: Applied Economics)
Calling to thank donors is considered a key fundraising strategy in the charitable giving industry. Yet the effectiveness of thank-you calls remains untested. We conduct field experiments with public television stations and a national nonprofit in which 500,000 new donors were randomized to receive a thank-you call or not. Fundraising professionals predicted that the calls$1 (Bwhich followed standard practices in the industry$1 (Bwould increase donor retention by 80 percent. In stark contrast, we found a precisely estimated null effect of calls on donor retention.- Reproduced s